Clove (Syzygium aromaticum) and brown algae (Sargassum sp.) Supplementation on Nutritional Content of Payangka Fish Nugget (Ophieleotris aporos (Bleeker) - Wisda Nurjannah Abdullah; Revolson Alexius Mege; Arrijani Arrijani; Yermia Semuel Mokosuli (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Payangka fish (Ophieleotris aporos (Bleeker)) is one of the most common fish species in Lake Tondano, North Sulawesi. Due to the availability of this fish throughout the year, it is one of the types of fish consumed by many people. However, the economic value tends to be below. This study diversified payangka fish into nuggets with clove spice (Syzygium aromaticum) and brown seaweed (Sargassum sp) supplementation. The research conducted aims to obtain a proximate profile and fatty acid content of payangka nugget. The research method used is an experimental laboratory method. The study consisted of preparing payangka fish, making payangka nuggets supplemented with clove and seaweed extracts, proximate analysis by gravimetric method and analysis of fatty acid content by gas chromatography method. The results showed that the supplemented payangka nugget had 67% water content, 0.80% ash content, 0.05% total fat, and 10.50% crude fiber. Omega 3 content is 4.75%, while Omega 6 content is 34.16%. Payangka fish nuggets that were supplemented had a higher nutritional content than those without supplementation. Payangka fish nuggets supplemented with clove extract and brown seaweed contain good dietary content.